The Saving of the Elderly in Micro and Macro Data - Weil, D. N. (Quarterly Journal of Economics, 1994)
Examination of household (micro) data on the elderly has generally concluded that they do not dissave significantly, whereas estimates using aggregate (macro) data have shown that the presence of a large elderly population leads to a lower saving rate. This paper shows that if interactions between generations are important, one would not expect these estimates to be the same. The paper presents new evidence that bequests are plausibly the source of this discrepancy. Examination of data from young households that have received or expect bequests confirms that bequests are indeed an important factor determining the saving of the young.